Recurrent respiratory papillomatosis (RRP) of tracheobronchial tree presenting as lung collapse with malignant transformation after a decade - Sai-on Ling; Yiu-fai Cheng; Pak-yuen Anthony Yau; Chie-wai Yim; Hoi-yee Kwan; Thomas Mok (Respiratory Medicine Case Reports, 2023)
Recurrent respiratory papillomatosis is a rare disease caused by HPV infection. We hereby report a patient with recurrent respiratory papillomatosis of the tracheobronchial tree with no laryngeal involvement who remained clinically stable for more than 10 years but then developed malignant transformation with metastases.A 61-year-old lady with good past health presented to our department in 2010 because of chronic cough for years. Chest X-ray showed reduced left lung volume. Bronchoscopy showed multiple nodules over left main bronchus and left upper lobe progressing to involve the posterior trachea and left lower lobe. Biopsy revealed squamous papilloma with mild dysplasia. She refused surgical intervention. She remained relatively stable until November 2022 when she developed left chest pain. CT showed features of malignant transformation with local invasion and metastases. Fine needle aspiration suggested squamous cell carcinoma. She succumbed in December 2022.Bronchoscopy should be considered in the investigation of unexplained chronic cough so that this rare disease can be detected at an early stage. The disease may not require intervention if uncomplicated. Despite clinical stability for a prolonged period, close monitoring for malignant transformation is warranted indefinitely.